2018
DOI: 10.1200/jco.2018.36.15_suppl.e18755
|View full text |Cite
|
Sign up to set email alerts
|

Survival and glycemic control in patients with colorectal cancer and diabetes mellitus.

Abstract: The impact of diabetes mellitus (DM) on survival in patients with colorectal cancer and the impact of colorectal cancer on glycemic control were examined. Materials & methods: Patients with colorectal cancer with and without DM were matched 1:1 (2007-2015). Characteristics were compared between the two groups and survival assessed with the Kaplan-Meier method. Mixed models compared hemoglobin A 1c and glucose levels over time. Results: In both groups, glucose values decreased during the year following cancer d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
2

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 20 publications
1
22
2
Order By: Relevance
“…origins), with use of matched case-control methods to compare overall survival (OS) between patients with and without DM. These analyses showed that DM did not significantly impact OS in studies of individual cancer types and no significant effect on BG levels was detected [12][13][14][15][16].…”
mentioning
confidence: 92%
“…origins), with use of matched case-control methods to compare overall survival (OS) between patients with and without DM. These analyses showed that DM did not significantly impact OS in studies of individual cancer types and no significant effect on BG levels was detected [12][13][14][15][16].…”
mentioning
confidence: 92%
“…Several investigators, including our team, reported the co-occurrence of diabetes mellitus (DM) and colorectal cancer (CRC) along with bowel inflammation and dismicrobism [16]. Moreover, multiple reports suggested the involvement of the gut microbiome in the evolution of DM, and that potential modulation of the intestinal microbiota could prevent or delay its progression [7]. Furthermore, data are increasing about the greater risk for CRC in patients with DM by almost 1.2% to 1.5% [8].…”
Section: Introductionmentioning
confidence: 99%
“…It appears that diabetes mellitus does not decrease the survival of the CRC patients and CRC does not have a significant impact on glucose level of patients with diabetes mellitus [53,54]. In a study with high risk of CRC in comparison to controls but only among men [55].…”
Section: Discussionmentioning
confidence: 87%